Association between melanoma and renal-cell carcinoma for sequential diagnoses: A single-center retrospective study. (December 2018) - Kim, Kunhwa; Chung, Tong Han; Etzel, Carol J.; Kim, Jinhyun; Ryu, Hyunjin; Kim, Dae Won; Hwu, Patrick; Hwu, Wen-Jen; Patel, Sapna P.; Liu, Mei; Kim, Kevin B.
Highlights: We found a strong association between the diagnosis of melanoma and RCC. Standardized Incidence Ratios (SIRs) for developing second primary melanoma among the RCC patients was 2.31. SIR for developing second primary renal cell carcinoma among the melanoma patients was 2.87. These increased risks could not be attributed to either immune status or previous anti-neoplastic treatment. Abstract: Background: Melanoma and renal-cell carcinoma (RCC) are known to be immunological neoplasms. Previous studies have shown increased risks in patients with melanoma of developing RCC and in those with RCC of developing melanoma. However, data regarding immunocompromised status in these patients are lacking. Methods: We conducted a retrospective review of patients who had a diagnosis of melanoma and/or RCC. Using summary statistics, we calculated total person-years at risk for developing melanoma among patients with RCC and for developing RCC among patients with melanoma, and compared the results with the SEER data. We also assessed medical history related to immune status and the use of immunosuppressive drugs. Results: Among 13, 879 patients with melanoma and 7597 patients with RCC, 89 had diagnoses of both melanoma and RCC (0.6% and 1.2% of melanoma and RCC patients, respectively): eight were diagnosed with both cancers concurrently, 54 were diagnosed with melanoma first, and 27 were diagnosed with RCC first. Standardized incidence ratios (SIRs) were 2.87 (95%CI 2.16–3.74) for developing RCC among the melanoma patients and 2.31 (95%CI 1.52–3.37) for developing melanoma among the RCC patients, compared to age-, sex-, race-, and calendar-specific adjusted incidence rates of each cancer in the SEER registry. None of the 81 patients with sequential diagnoses had a history of immunocompromised disease, nor did they receive chronic immunosuppressive drugs. Only two received chemotherapy and/or radiotherapy. Conclusion: We demonstrated a strong association between the diagnoses of melanoma and RCC. These increased risks could not be attributed to either immune status or previous antineoplastic treatment.